Restoration islands: a tool for efficiently restoring dryland ecosystems?. (29th October 2017) - Hulvey, Kristin B.; Leger, Elizabeth A.; Porensky, Lauren M.; Roche, Leslie M.; Veblen, Kari E.; Fund, Adam; Shaw, Julea; Gornish, Elise S.
Abstract : Restoration islands are concentrated plantings in strategic locations, created to efficiently use resources to achieve restoration goals. These methods have been used effectively in mesic ecosystems, particularly tropical forests, where the goal of island plantings is often to "nucleate" across a degraded area, providing a seed source for spread outside the planted area. Here, we consider how an island strategy might be used to achieve restoration goals in dryland ecosystems, where limited resources and large areas of degraded land make restoration extremely challenging. In contrast to more productive areas, spread or "nucleation" from restoration islands in drylands may not occur or occur more slowly than required by most management time frames. Despite this, small‐scale, more intensive island plantings may still be useful for achieving short‐term goals, such as weed control, fire management, erosion control, and creation of wildlife habitat. Over the long term, island plantings could serve the same nucleation function as in other ecosystems and serve as repositories for genetic diversity within highly fragmented native systems. Here, we highlight the opportunities for using these high‐intensity, targeted planting methods in dryland ecosystems, provide the guidelines for establishing islands to achieve short‐ and long‐term restoration goals, and identify the areas where additional research is needed to understand the value of restoration islands in dryland ecosystems.